People’s Participation in Knowledge Management of Laokhrang Cultural Community, Ban Kut Chok, Kud Chok Subdistrict, Nong Mamong District Chainat Province (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was a qualitative research with the objectives as follows: 1) to study the participation of people in the knowledge management of Laokhrang cultural community, Ban Kut Chok, Kud Chok sub-district, Nong Mamong district, Chainat Province at present, and 2) to study the supporting factors and factors that impede public participation in knowledge management of Laokhrang Ban Kut Chok cultural community, Kud Chok sub-district, Nong Mamong district, Chainat Province. The population used in this research was academics, local administrators, community developers, assistant district chief officer, sheriffs, community leaders, folk scholars in the amount of 30 people and conducted a specific interview. Results indicated that 1) Participation of people in knowledge management of the Laokhrang Ban Kut Chok cultural community, Kud Chok sub-district. Nong Mamong district , Chainat province at present was at a moderate level. 2) Factors influencing the participation of people in knowledge management of the Laokhrang Ban Kut Chok cultural community, Kud Chok sub-district, Nong Mamong district, Chainat Province were as follows : 2.1 The supporting factors affecting the participation of people, government agencies and the private sectors had played a role in promoting the participation of people in many areas, such as study visits, budgets, etc. with the goal to restore culture , good traditions of the community as well as Laokhrang culture in Ban Kut Chok , Nong Mamong district, Chainat province in order to maintain and have representatives to carry on the tradition. 2.2 The problem with public participation was that the majority of people was focused on high-income and stable careers, abandoning their agricultural careers and their homelands. The rest of the people in the community was mostly the elderly. If in the future, the condition of Laokhrang culture in Ban Kut Chok, Nong Mamong district, Chainat Province continues to be this way, the good traditions of the community will be lost over time.